Removal of rubber earphonecover inside nose after 2 years in a general practitioner setting during covid-19 pandemic - Zainun, Zuraida; Hadi , Azliehanis Abd (Bangladesh Journal of Medical Science, 2022)
Inserted a big size of rubber ear phone cover into the nose is a rare case.Foreign body regarding children is common and need to be seriously considered.Nowadays, using an earphone for music players and games isverycommon among children that need to be more cautious.In general practitioner’s practice, several limitations seen with no fully equipped and emergency trolley, no general anaesthetic set up and no X ray. In this case report, we reported a 10-year-old child with bad smelling breath for 2 years with on and off pain and difficulty in breathing. It has become worsened until the child informshis mother regarding this incidence last weeks. Last 2 weeks, the child was examined in dental clinic for this bad smelling breath and no dental problem identify. The parents were refused to bring the child to the hospital because of this Covid-19 situation worsening in this state currently. They decided to cometo nearby general practitioner where the smelly and soaked with pus in this ear was removed without any complication in that clinic without any anaesthesia using blunt crocodile forceps. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 467-469